Hospital solid waste management system to reduce the environmental impact in a hospital social segurity the Tacna – 2018 - Herrera Rojas, Milagros (2020)
The objective of this study was to elaborate a proposal of a hospital waste management System to reduce the environmental impact in the Hospital III Daniel Alcides Carrión of Tacna. The design of this research was non experimental, transversal and prospective because of the realization of a basal diagnostic to the characterization of the hospital waste in a period of seven days, and to valorize the components of hospital waste management were applicate evaluation cards as it is indicated in the Technical Health Standard of Peru NTS N° 096- MINSA/DIGESA this procedure of evaluation permit to identify the environmental impact generated because of the inappropriate  waste management in all their stages. The results showed that the type of waste which is generated the most is biocontaminated with 391 kg/day followed of the common waste with 112 kg/day and at last the special waste with 17 kg/day. Related to the compliance of the administrative aspects and waste management in the hospital as the NTS N° 096- MINSA/DIGESA said: for the waste management stages it obtained a valuation of good, secondly for the compliance of waste management aspects it obtained a valuation of good with a punctuation of 30. There for this results have permitted to elaborate a proposal of hospital waste management system to reduce the environmental impact at the Hospital III Daniel Alcides Carrión of Tacna, document that will allow to strengthen and improve the suitable hospital waste management and contributes to the prevention and control of the sanitary and environmental pollution.